FAKTOR - FAKTOR YANG MEMPENGARUHI PENERAPAN SAK ETAP PADA UMKM DI KOTA BATAM - Sanglise, Yanti; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2022)
This study aims to analyze the factors that influence the application of SAK ETAP to MSMEs in Batam City. The sample in this study were micro business actors in Batam City as many as 87 respondents who were taken using purposive sampling technique. The data collection technique used in this research is by distributing questionnaires to the respondents. Testing the data in this study using linear regression analysis with a significant level of 5%. The results showed that educational background and age of business did not affect the application of SAK ETAP, while socialization and training affected the application of SAK ETAP.